Studies and prospectives of mechanically harvested ratooning rice in China - Ting Chen; Peiying Weng; Chaojie Lan; Fallah Nyumah; Chunlin Guo; Wenfang Lin; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Technology in Agronomy)
Continuous improvement of rice breeding methods and consecutive innovation of cultivation technology in China has resulted in a significant increase in the proportion of ratooning rice planting mode. Therefore, ratoon rice has become a prominent rice planting pattern in China. This study reviewed the current situation and prospects regarding ratoon rice's high-yielding formation and physiological mechanisms. We focused on four key aspects: screening and breeding of ratoon rice cultivars, classification, determining suitable stubble height, and water and fertilizer management considerations for rice ratooning. Additionally, we delved into characteristics related to dry matter production and allocation in ratoon rice. This study also explored the regenerative activity and root vigor within the rhizosphere zone while evaluating their relationship with micro-ecological characteristics specific to ratoon rice. We propose the implementation of proper regulation precise over the rhizosphere environment aimed at scaling up sustainable progress in the realm of research, aimed at expanding the utilization of mechanized low-cut stubbles (< 25 cm) for the advancement of the ratoon rice sector. This process is essential for stimulating the availability of vital soil nutrients to promote timely sprouting axillary buds while facilitating tiller growth coordination along with bud elongation, collectively referred to as achieving 'four highs' (high regeneration coefficient, high effective panicle percentage, high harvest index, and high daily yield) alongside 'one low' (low carbon emission) for safe and sustainable development purposes. Furthermore, we have also put forward corresponding policy recommendations in light of the challenges encountered during the development process of the ratoon rice industry.